Flipped-Differentiated Learning (FDL) as an Innovative Learning Model to Improve Learning Outcomes - Tri Purwaningsih (UM Purwokerto Press, 2025)
The Flipped-Differentiated Learning (FDL) model is an innovative approach that combines the concepts of Flipped Classroom and Differentiated Instruction to enhance student learning outcomes. This model allows students to access materials before class, while class activities are focused on problem-solving and deeper interactions. The purpose of this research is to examine the effectiveness of the FDL model in improving student learning outcomes compared to conventional learning models. The research method used is an experiment with a pretest-posttest control group design. The results of the study indicate that the implementation of FDL significantly improves student learning outcomes, particularly in conceptual understanding and active engagement in learning. The implications of this research suggest that FDL can be an effective solution in more flexible learning that meets the individual needs of students.